Math Anxiety and Working Memory Updating: Difficulties in Retrieving Numerical Information From Working Memory - Pelegrina, Santiago; Justicia-Galiano, M. José; Martín-Puga, M. Eva; Linares, Rocío (Frontiers in Psychology, 2020)
This study aimed to determine whether math anxiety was related to working memory updating performance and, specifically, to the retrieval and substitution components of updating. A set of working memory updating tasks that involve different retrieval and substitution requirements were administered to one hundred and fourteen university students. In addition, participants completed a math anxiety assessment on two occasions: 1–2 weeks before and immediately prior to task administration. The results showed a relationship between math anxiety scores and updating performance. Math anxious individuals took longer and made more errors, especially on tasks that required retrieving information from working memory. These results suggest that math anxious individuals are less efficient when it comes to accessing numerical information in working memory. Consequently, they may struggle with math-related tasks that involve retrieving information from working memory.